Risk Management Practices among Private Equity Funds in South Africa - Zerihun, Mulatu Fekadu; Affedjou, Beringer Moresque (International Journal of Economics and Financial Issues, 2025)
Effective risk management is essential for private equity (PE) funds to navigate economic, market, and operational challenges while maximizing investor returns. This study aims to evaluate the risk management practices employed by private equity funds in South Africa, focusing on the tools used for pre-investment risk assessment and the strategies implemented throughout the investment process. A quantitative approach was adopted, using a semi-structured questionnaire administered to 31 private equity fund managers in South Africa’s Gauteng province. The Mann-Whitney U test, a non- parametric statistical method, was applied to assess the independence of smaller and larger fund groups, given their distinct nature and the non-normal distribution of the dependent variable. The findings indicate that traditional pre-screening risk assessment methods are commonly used by South African private equity funds. Additionally, larger funds tend to co-invest with trusted partners as a key strategy for mitigating risk. The results also reveal that these larger funds more frequently utilize the enterprise value/earnings before interest and tax (EV/EBIT) ratio in their evaluation process. This study supports the Basel II recommendation, which suggests that adopting an audit and risk planning framework can help private equity firms identify the most critical risks and concentrate their risk management efforts accordingly. The survey’s overall results show that cash flow-volatility-based models and stress testing are the most widely utilized tools among the funds studied. This research contributes to the ongoing discourse on risk management in private equity, particularly in the context of South Africa’s emerging economy, offering new insights into a relatively underexplored area.